Study on pedestrian and cyclist interactions at signalised bicycle-cum-pedestrian crossings - Pua, Zheng Jie (2019)
In recent times, cycling is becoming an increasingly popular and acceptable form of transportation in Singapore. Many facilities such as the park connectors have been developed to incorporate cycling as a mode of transport. As Singapore moves towards a bicycle-friendly city, there is a legitimate concern about the impacts on space-sharing between pedestrians and cyclists on shared-space amenities as Singapore is a small country with limited land area. To ease the concern on space-sharing, Singapore has installed various infrastructure such as the signalised bicycle-cum-pedestrian crossings to facilitate the development of cycling as a form of sustainable mode of transport. This project studies the effectiveness of signalised bicycle-cum-pedestrian crossings since a long time after implementation. It also analyses the actions of cyclists at signalised bicycle-cum-pedestrian crossings and signalised pedestrian-only crossings since a long time after implementation. The sites selected for research in this project were the signalised bicycle-cum-pedestrian crossings at Tampines Avenue 4 and Tampines Avenue 3 near Block 831, and the signalised pedestrian-only crossing at Tampines Avenue 3 near Block 819. Perception surveys were carried out for the signalised bicycle-cum-pedestrian crossing at Tampines Avenue 4 to gather cyclists’ perceptions and attitudes towards the crossing zone. The results of the perception surveys showed that 88% of the respondents stated that they would adhere to the designated bicycle crossing lane at the signalised bicycle-cum-pedestrian crossing in Tampines Avenue 4. The results also showed that 54.5% of the respondents observed improvements at the signalised bicycle-cum-pedestrian crossing since it was first implemented. GoPro cameras were mounted at the selected signalised bicycle-cum-pedestrian crossings and signalised pedestrian-only crossing to record the behaviours of cyclists at these crossing zones. The video footages collected showed that 63% of the cyclists followed the designated bicycle crossing lane at the signalised bicycle-cum-pedestrian crossing at Tampines Avenue 4 while 70.2% of the cyclists followed the designated crossing lane at the signalised bicycle-cum-pedestrian crossing at Tampines Avenue 3 near Block 831. Records of the video footages also showed that 96.2% of the cyclists cycled across the signalised bicycle-cum-pedestrian crossing at Tampines Avenue 4. Over at Tampines Avenue 3, it was observed that 99.1% of the cyclists cycled across the signalised bicycle-cum-pedestrian crossing near Block 831 while 100% of the cyclists cycled across the signalised pedestrian-only crossing near Block 819.